2014
DOI: 10.1177/1060028014540868
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Prescribing Dabigatran Etexilate and Rivaroxaban in Patients With Nonvalvular Atrial Fibrillation

Abstract: Inappropriate use of DE and rivaroxaban in patients with NVAF is frequent and possibly leads to AEs. Reinforcing education of health care professionals and patients is needed. Collaboration with clinical pharmacists can contribute to better use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 48 publications
5
81
0
2
Order By: Relevance
“…This finding is consistent, albeit with a greater incidence, with findings in the study by Larock and others, 6 in which 26% of patients were receiving an inappropriate dosage of rivaroxaban or dabigatran.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is consistent, albeit with a greater incidence, with findings in the study by Larock and others, 6 in which 26% of patients were receiving an inappropriate dosage of rivaroxaban or dabigatran.…”
Section: Discussionsupporting
confidence: 81%
“…In a recent study, 49% of patients were receiving dabigatran or rivaroxaban inappropriately as a result of, among other reasons, inappropriate medication choice, prescription of the wrong dosage, or improper administration (e.g., rivaroxaban taken on an empty stomach). 6 In another study, 19% of patients were receiving an inappropriate dose of a direct oral anticoagulant, and an additional 14% were using their direct oral anticoagulants inappropriately. 7 However, a literature search conducted in April 2016 revealed that the appropriateness of apixaban prescribing had not been specifically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns with the safety and the potential budget impact of dabigatran when prescribed in more elderly co-morbid populations that those recruited into Phase III clinical trials (13,41,117). These concerns resulted in a number of professional bodies and health authorities initiating extensive preand peri-launch programmes, some of which are listed in Table A1 (Appendix).…”
Section: Ii) Dabigatran To Prevent Stroke and Systemic Embolism/clot mentioning
confidence: 99%
“…6 Additional data suggest that serum dabigatran levels can vary widely when administered correctly 4 and that off-label prescribing, incorrect dosing and dosage administration errors are not uncommon. 7 We analyzed time trends in atraumatic intracranial bleeding treated at a Canadian neurosurgical centre during the period when the direct oral anticoagulants were introduced.…”
mentioning
confidence: 99%